Metode problem based learning dalam Pembelajaran Fiqih Berbasis Kitab Fathul Qarib di Pondok Pesantren Raudlatul Ulum 1 - Raudlatul Jannah; Luqman Hakim (Mu'allim, 2025)
This study aims to implement problem-based fiqh learning (PBL) through the Fathul Qarib book discussion activity at the Raudlatul Ulum 1 Putri Islamic Boarding School, and to analyze its impact on the involvement of students in learning. The problem-based learning model (PBL) is applied in the form of student deliberations that raise real problems and find solutions based on fiqh arguments. This study uses a qualitative approach with a case study method. Data collection techniques include observation, interviews, and documentation, which are explained thematically. The results of the study indicate that the application of PBL in fiqh discussions encourages increased fiqh skills, learning independence, discussion ethics, and students' self-confidence. Students not only understand the text of the book passively, but actively bring up contextual problems, formulate solutions based on arguments, and discuss with manners. Thus, this learning model is effective in forming a scientific culture and affective attitude of students, and is relevant to be developed as a pedagogical approach in the Islamic boarding school environmen.